The Relationship between Word of Mouth and Consumer Buying Behavior Mediating by Religious Orientation in Riyadh, Saudi Arabia - Auf, Mohamed Abdellatif Abu; Salleh, Salniza Bt Md.; Yusoff, Rushami Zien (International Review of Management and Marketing, 2016)
This paper investigated the relationship of word of mouth, media and consumer buying behavior to leapfrog marketing which is strongly related with the issues of psychology and sociology. The prime objective of present research is to analyze the market and the consumer behavior by taking religious orientation as a mediator which is found to be statistically significant. An extensive literature review related to the religious orientation, word of mouth, consumer buying behavior and media has been carried out by the researcher. In addition, present study used survey questionnaire in order to collect quantitative data from the respondents who have been using cars in “Riyadh”, the capital city of Saudi Arabia, for highlighting the factors affecting cars buying behavior of consumers. The data was collected from car agencies in Riyadh indicating that religious orientation play a significant role between word of mouth and media in the field of consumer buying behavior. The limitations of this research and direction for future research are also given at the end. Keyword: Religious Orientation, Word of Mouth, Consumer Buying Behavior JEL Classifications: M31, Z12